TEKNIK PEMANGKASAN TANAMAN KOPI (Coffea sp) - Renan Subantoro; Mukhamad Abdul Aziz (Universitas Wahid Hasyim, 2019)
Production of smallholder coffee crops is not maximal because the crop maintenance factors are mostly in terms of proper pruning techniques. Through this article, it is hoped that the information and field experience of coffee cropping techniques needed by smallholder coffee farmers will need to increase the production of coffee produced by the good quality of the coffee produced. The purpose of trimming coffee crops is to improve the shape of the tree, improve quality and production, and facilitate maintenance and harvesting. The writing method of this paper was compiled by examining various literature and field assessments of coffee crop trimming techniques to improve the quality of coffee production. As a result of the study in this paper: Trimming forms for coffee crops so that strong crops and crops are balanced in forming Plagiotropic branches, both primary and secondary branches. It should be noted is how to treat the coffee crop itself to support the success of cultivation. Maintenance pruning activities are basically aimed at maintaining the continuity of the plant skeleton obtained from pruning the form by removing unproductive branches. Keywords: coffee, maintenance, form of pruning.